The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1590/s0102-33062003000400008
|View full text |Cite
|
Sign up to set email alerts
|

Flora vascular de açudes de uma região do semi-árido da Bahia, Brasil

Abstract: Foram selecionados seis açudes que margeiam a Estrada do Feijão (BA 052), nos municípios de Feira de Santana e Angüera, entre as coordenadas 39º30'-39º00'W e 12º00'-12º30'S. Com a finalidade de se conhecer a flora vascular dos mesmos, esses tipos de plantas foram coletadas de agosto/1996 a dezembro/1997. Registraram-se 121 espécies distribuídas em 46 famílias. As famílias mais representativas foram: Cyperaceae, com 18 espécies (14,9%), Poaceae, com 13 (10,7%), Asteraceae, com 10 (8,3%), Scrophulariaceae e Faba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1
29

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 2 publications
(2 reference statements)
1
13
1
29
Order By: Relevance
“…Many studies have demonstrated the influence of these plants on the communities of benthic macro-invertebrates ( Van den Berg et al, 1997;Takeda et al, 2003), fishes (Agostinho et al, 2003;Pelicice et al, 2005;Sánchez-Botero et al, 2008), periphyton (Pompêo and Moschini-Carlos, 2003), and zooplankton (Lansac-Toha et al, 2003). Floristic inventories have provided essential information for the conservation of biodiversity (Camargo et al, 2003;França et al, 2003;Matias et al, 2003;Paz and Bove, 2007;Rocha et al, 2007;Mora-Olivo and Villaseñor, 2007;Martins et al, 2008;Pivari et al, 2008a).…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have demonstrated the influence of these plants on the communities of benthic macro-invertebrates ( Van den Berg et al, 1997;Takeda et al, 2003), fishes (Agostinho et al, 2003;Pelicice et al, 2005;Sánchez-Botero et al, 2008), periphyton (Pompêo and Moschini-Carlos, 2003), and zooplankton (Lansac-Toha et al, 2003). Floristic inventories have provided essential information for the conservation of biodiversity (Camargo et al, 2003;França et al, 2003;Matias et al, 2003;Paz and Bove, 2007;Rocha et al, 2007;Mora-Olivo and Villaseñor, 2007;Martins et al, 2008;Pivari et al, 2008a).…”
Section: 2mentioning
confidence: 99%
“…Both families contain many taxa of aquatic macrophytes (França et al, 2003;Matias et al, 2003;Rocha et al, 2007;Pivari et al, 2008b). Some species of these families can colonize a wide variety of aquatic environments and inhabit ecotone areas (Cook, 1996;Leite et al, 2009).…”
Section: 2mentioning
confidence: 99%
“…Many studies have demonstrated the influence of these plants on the communities of benthic macro-invertebrates ( Van den Berg et al, 1997;Takeda et al, 2003), fishes (Agostinho et al, 2003;Pelicice et al, 2005;Sánchez-Botero et al, 2008), periphyton (Pompêo and Moschini-Carlos, 2003), and zooplankton (Lansac-Toha et al, 2003). Floristic inventories have provided essential information for the conservation of biodiversity (Camargo et al, 2003;França et al, 2003;Matias et al, 2003;Paz and Bove, 2007;Rocha et al, 2007;Mora-Olivo and Villaseñor, 2007;Martins et al, 2008;Pivari et al, 2008a).…”
Section: Introductionmentioning
confidence: 99%
“…A diversidade florística de reservatórios do Nordeste do Brasil é bem estudada no âmbito de pesquisas envolvendo macrófitas (FRANÇA et al, 2003;MOURA JÚNIOR et al, 2011). Contudo, França et al (2003), em estudos de distribuição de macróitas em reservatório, observaram que a forma biológica que apresentou maior abundância nas coletas foi a forma Anfíbia (73%).…”
Section: Introductionunclassified
“…Contudo, França et al (2003), em estudos de distribuição de macróitas em reservatório, observaram que a forma biológica que apresentou maior abundância nas coletas foi a forma Anfíbia (73%). Deste total, boa parte enquadrava-se como espécies ruderais, ou seja, espécies cultivadas nas margens do reservatório (FRANÇA et al, 2003).…”
Section: Introductionunclassified